Serum selenium level in acute myocardial infarction - Abdallah I Ali Kelani; Hanan S El-Deen Mohammed; Mona M Soliman; Marwa Sayed; Hala M El-Badre; Mai A Fathi (SpringerOpen, 2018)
Introduction Although remarkable developments have been made in the management of cardiovascular disease, myocardial infarction (MI) remains the most common cause of death worldwide. MI is an acute condition of myocardial cell death that occurs as a result of imbalance between the coronary blood supply and myocardial requirements. Lipid peroxidation and excessive production of reactive oxygen species (ROS), such as superoxide anions (O2•−) and hydrogen peroxide, play a major role in the mechanism of MI. ROS directly damage the cell membrane and cause cell necrosis. However, ROS also stimulate signal transfer to upregulate inflammatory cytokines, for example, tumor necrosis factor-α in the ischemic area and the neighboring myocardium. Aim The aims of this article were: (a) to determine serum selenium (Se) and the cut-off value in acute MI patients and the correlation between serum Se and other cardiac biomarkers such as troponin, creatine kinase (CK), creatine kinase myocardial brand (CK-MB), C-reactive protein, and lipogram; and (b) to determine the most predictor risk factor of MI. Materials and methods The study was carried out on 120 individuals (60 patients and 60 controls). The patients presented to the Internal Medicine Department and Coronary Care Unit at Assiut University Hospital. The healthy controls were selected and matched for age and sex, and only those who were found to be in good health and free from any signs of chronic diseases or disorders were included. Results The main finding of this analysis that there is a statistical difference between patients and controls in serum Se as the mean Se level in patients was 80.3±20.5 and in controls it was 97.2±14.0 and P value of less than 0.001, Thus, serum Se is significantly low in MI patients. Also, there was no statistical difference in serum Se in terms of sex, smoking, accompanying diseases (diabetes or hypertension), or type of infarction. Conclusion This study supports a significant association between deficient serum Se concentration with cut-off value of up to 84 ng/ml and MI. Strikingly, the most predictor of MI is serum Se, followed by total cholesterol, diabetes mellitus, low-density lipoprotein, and hypertension.